Filter packed with Al-sludge waste for phosphorus removal as a polishing system in a wastewater treatment plant - Garzón-Zúñiga, Marco A.; Navarro-Franco, Javier Alejandro; Moreno Andrade, Iván (Tecnología y ciencias del agua, 2024)
Recently, using residual aluminum sludge (Al-sludge) from drinking water treatment plants for phosphorus removal has been assessed and it has shown to be highly efficient. However, most of the studies have been conducted using synthetic water. Only a few works have applied this method to real wastewater (WW), and none of them have been tested in continuous mode, as a polishing step, in a pilot-scale, decentralized wastewater treatment plant (WWTP). This paper aimed to evaluate the performance of an immersed filter packed with a bed of residual Al-sludge as a polishing system for Phosphorous removal, in a pilot-scale, decentralized WWTP. The study determined at laboratory-scale the capacity for phosphorus removal through batch and continuous tests using both synthetic and real wastewater and evaluated the effect of retention time. Based on the results, an Al-sludge immersed filter (Al-sludge Filter) at pilot-scale was constructed, implemented, and evaluated as a polishing step for the effluent of a decentralized-WWTP. The results showed that during continuous testing with real WW, the phosphorus removal capacity was 2.55 mg P-PO43-∙g-1 per gram of Al sludge using a retention time of 120 min. The Al-sludge filter as a polishing system presented an average removal efficiency of 94 ± 8 % and an effluent concentration of under 0.50 mg P-PO43-∙l-1 during the first 20 operational days. For the next 17 days, the system removed 85 ± 9 % on average, showing an effluent concentration of under 1.0 mg P-PO43-∙l-1. From operational day 32 onwards, the removal efficiency was 63.6 ± 10.7 %, with an average effluent concentration of 2.20 ± 0.39 mg P-PO43-∙l-1.